Reconsidering southern labor history : race, class, and power - Hild, Matthew; Merritt, Keri Leigh, 1980- (University Press of Florida, 2018)
Reconsidering Southern Labor History: Race, Class, and Power presents fresh and original scholarship that reexamines and reinterprets the field. Collectively, these essays cover virtually the entire span of United States history, from the early national period following the American Revolution through the twenty-first century. The essays that examine the antebellum South will demonstrate that the problems of southern labor in that era still carry relevance in the twenty-first century and merit scholars' attention.